Role of thermodynamic miscibility gaps in phase selection in sol-gel synthesis of yttrium silicates. Issue 15 (December 2017) - Anantharaman, Surendra B.; Rajkumar, V.B.; Raghunandan, S.; Hari Kumar, K.C.; Kumar, R. Suresh; Gandhi, Ashutosh S.
Abstract: Yttrium monosilicate and disilicate are important materials for environmental barrier coatings. The two silicates were synthesized by sol-gel route and their phase selection upon calcination and thermal exposure was studied. First products of crystallization were the monosilicate and yttria. Amorphous silica precipitated out at 1300 °C as apatite phase. During prolonged high temperature treatment, up to 100 h at 1400 °C, the apatite disappeared and the disilicate appeared, only to disappear itself as the system approached equilibrium. Thermodynamic calculations performed using Thermo-Calc software show the presence of a metastable miscibility gaps in the amorphous (liquid) phase field. As a consequence, phase separation in the amorphous phase prior to crystallization is responsible for the formation of yttria-rich and silica-rich phases during crystallization. Multiple phase formation during both, yttrium monosilicate and disilicate synthesis is consistent with the presence of the amorphous phase miscibility gaps around the silicate compositions.